Understanding the Physiology of Adipose Tissue: A Key to Combat Obesity? - Muralidhara DV (Journal of Obesity Management, 2016)
Human obesity is now universal and has drawn serious attention of international academia to unravel its pathophysiology and treatment. In recent years, efforts are being made to understand the complex physiology of both white and brown adipose tissue in detail with relevance to obesity. A large number of secretions from the white fat called the adipokines have been recognized that play a definitive role in obesity and its disorders. Innumerable regulators grouped mainly under the transcriptional, hormonal and signaling factors that govern the thermogenic functions of brown fat have been worked out. Based on these revelations, strong suggestions have been made for treating obesity specially by targeting the brown fat as it plays a key role in energy expenditure as well as through behavioral, pharmacological, physiological and surgical approaches. Such findings have been reported in a nutshell in this communication
Keywords: Adipose tissue